Evaluation of the effectiveness of yoga in management of premenstrual syndrome: a systematic review and meta-analysis. (2nd October 2022) - Pal, Arghya; Nath, Banashree; Paul, Sayanti; Meena, Snehlata
Abstract: Aim: The management of Premenstrual Syndrome (PMS) is still evolving due to the modest effect sizes of the available treatment modalities. Yoga as therapeutic intervention in PMS has been gathering interest amongst researchers. The current manuscript reviews the evidence surrounding yoga in PMS. Methods: This manuscript was a systematic review and meta-analysis evaluating the effectiveness of yoga on the total scores and sub-domains of PMS after studies were identified using a pre-defined selection criterion after a search in PubMed, Google Scholar, Scopus and Web of Science. Both quantitative and qualitative analysis of the accumulated data was performed. Overall, 14 studies were identified for the review, 11 of which were used for the purpose of quantitative analysis. Results: The studies were heterogenous in terms of the design, yoga regimes, nature of interventions and tools used for outcome measures. It was found that yoga was beneficial in the management of PMS. This benefit was also seen when all the sub-domains of PMS were individually examined except physical sub-domain. Conclusion: Though there were certain limitations in our review like heterogeneity in studies, possibility of publication bias and restrictive selection criterion; it supported that yoga can be beneficial in patients with PMS.